Characteristics of Early Maillard Reaction Products by Electrospray Ionization Mass Spectrometry - Li, Chuanjiang; Wang, Hui; Zhang, Yinfeng; Juarez, Manuel; Shao, Guangjie; Dongliang Ruan, Eric (Asian Journal of Chemistry, 2014)
It is crucial to characterize early Maillard reaction products and the important compounds formed in the early stage of Maillard reactionas Amadori rearrangement products are the most important modifications in food science. We report here that using electrospray ionization-mass spectrometry (ESI-MS) to directly characterize fragmentation behaviour of Amadori rearrangement products in a reaction model system using six selected amino acids (arginine, asparagine, glutamine, histidine, lysine and tryptophan) and their N-terminal acetylated forms with two reducing disaccharides, lactose and maltose. The fragmentation behaviour of Amadori rearrangement products was illustrated by Tandem MS (MS2) with collision-induced dissociation (CID). Results showed that the sugar moiety was preferentially fragmented, where by the neutral loss of small molecules, such as 18 Da, 36 Da, 216 Da, 246 Da and 324 Da from disaccharide moieties. Among the fragmented ions, [M-246 + H]+ of disaccharides were relatively stable and they were further studied for fragmentation mechanisms based on representatives of lysine and Na-Ac-lysine. The study is useful to understand the fundamentals of glycation in complex protein systems based on ESI-MS related techniques.